Seroprevalence of Neospora caninum in Local Breed chickens in AL-Fallujah District, Iraq. - Ayoub Ibrahim Ali Al-Jumaily; Haider Mohammed -Ali Al-Rubaie (مجلة الانبار للعلوم البيطرية)
This study was conducted to study the prevalence of Neospora caninum in the local breed chickens in Al- Fallujah district, Iraq. One hundred and eighty (91 males and 89 females) were purchased from four regions (Al-Fallujah Center, Al-Shehabi, Al-Saglawia and Al-Karma ) for study the effects of sex, and months in the infection rate. Blood samples collected and sera were isolated for (c-ELISA) during the period from December 2018 to September 2019. The total infection rate was 9.4% and there was highly significant(P≤0.01) difference between the females 11.2% (10/89) and males 7.6% (7/91) infections. Regions of Al- Fallujah district showed highly significant (P≤0.01) difference in the infection rates that were ranged between 4.5% (2/44) in Al-Fallujah Center to 14.5% ( 7/48) in Al-Shehabi. The highest infection rate was demonstrated in May 25% (6/24) compared with December, July and August that were recorded 5% (1/20) with significant(P≤0.01) difference, and no infection rate was recorded in the January and February months. In conclusion ( it is the first study that described the infection rate of N. caninum in the local breed chickens) in Al- Fallujah district, Iraq.